2022
DOI: 10.3389/fpsyg.2022.858521
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Users’ Psychological Needs on Relationship Quality in Short Video Applications

Abstract: Along with the rapid development of big data, artificial intelligence, and information technology, the relationship quality (RQ) between short video applications and users is important for the sustainable development of short video applications. However, the existing studies have explored the mechanism of the role of RQ in a limited way. In order to respond to this critical issue, this study constructs a theoretical model based on attachment theory and combined with self-determination theory, with autonomy nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The messages on sustainability were found to favorably influence consumers' viewpoints, and awareness and boost eWOM [87,88]. Additionally, previous studies found that attachment, trust, and identification were elements of relationship quality [89][90][91]. Furthermore, relationship quality can have a positive impact on eWOM [92].…”
Section: Electronic Word-of-mouth (Ewom)mentioning
confidence: 85%
“…The messages on sustainability were found to favorably influence consumers' viewpoints, and awareness and boost eWOM [87,88]. Additionally, previous studies found that attachment, trust, and identification were elements of relationship quality [89][90][91]. Furthermore, relationship quality can have a positive impact on eWOM [92].…”
Section: Electronic Word-of-mouth (Ewom)mentioning
confidence: 85%
“…However, despite the higher quality of longer videos, this does not necessarily correlate with higher popularity. The number of likes, comments, and shares, which reflect video popularity [27], were negatively correlated with DISCERN scores. This suggests that TikTok users are more likely to interact with lower-quality videos, possibly due to the platform's entertainment-oriented nature [28].…”
Section: Correlation Between Video Quality and Characteristicsmentioning
confidence: 98%
“…Compared with text and pictures, short videos are more visually appealing ( Lu et al, 2022 ). Accordingly, people are increasingly inclined to use short videos to quickly and effectively learn new travel information ( Huangfu et al, 2022 ). The ability to freely access the information they need from short videos evokes a sense of freedom in users, which leads to a demand for autonomy.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…For example, users make a 3–5 min short video of their own travel experiences and upload it to the platform: other users may watch it, comment on it, or like it. Producers can enhance their influence based on how many comments and likes the video received ( Huangfu et al, 2022 ; Zhao and Shi, 2022 ). In this process, users gain attention and recognition from others by posting videos, interacting with other users, and liking videos, resulting in a sense of self-fulfillment, which satisfies their desire for competence.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%